Risk Stratification in Patients with Coronary Artery Disease: Timeliness of Invasive Interventions - Olga I. Nishkumay; Oksana I. Rokyta; Illia A. Kordubailo; Aza A. Kovalenko; Artem O. Govorov; Igor I. Gorda; Svitlana M. Dubynska; Marta Yu. Vibla; Nataliia O. Pidmurniak (Ukrainian Journal of Cardiovascular Surgery, 2022)
Coronary artery disease (CAD) remains a top cause of morbidity and mortality nowadays. Current guidelines are used to deϐine timely diagnostic and management strategies for a patient with new angina symptom. According to the guidelines, the main purpose is assessment of the pretest probability of obstructive CAD. Exercise electrocardiography is the most accessible methodwith 85-90% speciϐicity and 45-50% sensitivity. Cardiopulmonary exercise testing (CPET) with concomitant monitoring of electrocardiogram, heart rate and blood pressure, expired gas analysis has become widespread among different exercise tests. CPET is an important clinical tool to estimate exercise capacity. In most cases it allowsto determine the causes of limited physical activity, evaluate both the blood supply (pulmonary, cardiovascular, haematopoietic systems) and tissue oxygen metabolism (skeletal muscle system) in response to physical exercise.The indications for invasive coronary angiography include: high clinical risk of CAD, symptoms which are refractory to medical therapy, low tolerance to exercise or if revascularization is considered for improvement of prognosis.The aim. To highlight the need for a combination of non-invasive stresstesting (CPET, stress echocardiography) and invasive testing (such as coronary angiography) to develop proper tactics of treating patients with established CAD.Conclusion. Described clinical case demonstrates preferences of combined different functional non-invasive tests (CPET, stress echocardiography) in a patient with confirmed CAD, who received prognosis modifying therapy and had high exercise tolerance due to regular cardio training. This gave the reason for postponing the repeated ICA to determine the dynamics of the progression of coronary atherosclerosis. However, when an anginal attack occurred and repeated urgent ICA was performed, it became necessary to perform coronary artery bypass grafting and, later, due to the continuation of anginal attacks and the presence of areas of ischemia, stenting of the trunk of the left coronary artery.